Association of mental health with myopia among children and adolescents: a cross-sectional survey in Shandong province - Hui WU; Long-tang XIE; Yuan-yuan HU (Editorial Office of Chinese Journal of Public Health, 2022)
ObjectiveTo explore the correlation between mental health and myopia in children and adolescents and to provide evidences for developing strategies on myopia prevention.MethodsUsing stratified cluster sampling, we recruited 10 720 students of grade 3 - 8 from 52 primary/junior high schools in 13 urban districts and 13 counties across Shandong province. The students' visual acuity was examined with Standard Logarithm Eyesight Table and computer refractometer during September - December 2020 and their mental health status were assessed simultaneously online with the Mental Health Scale for Child and Adolescent (MHS-CA) developed previously by domestic researchers. ResultsComplete information were collected from a total of 8 672 students (53.9% boys and 46.1% girls, 79.5% primary and 20.5% junior high school students). Compared to the non-myopic students, the myopic students had significantly higher MHS-CA dimension scores for thinking (17.25 ± 2.87 vs. 17.12 ± 2.86, t = - 1.97) and emotion (10.69 ± 1.93 vs. 10.57 ± 1.96, t = - 2.67) (both P < 0.05). The differences in MHS-CA dimension scores for thinking, emotion and volitional behavior between myopic students and non-myopic students became significant with the age increase of the students. There was a significant difference in MHS-CA score among the students in different geographical regions. The occurrence and development of myopia in the students differed significantly by gender (t = - 38.85), schooling grade (t = - 6.75), residence region (t = 4.26), and MHS-CA score for emotional dimension (t = - 2.63) (all P <0.05). ConclusionThe prevalence of myopia in children and adolescents of Shandong province is related to gender, age, residence region, and mental status and the impact factors need to be concerned in myopia prevention in the younger population.